Current status of clinical research on chronic obstructive pulmonary disease related fatigue (慢性阻塞性肺疾病相关性疲劳的临床研究现状) - KOU Xuemei (寇雪梅); LI Xinxia (李新霞) (Journal of International Translational Medicine Limited, 2021)
Fatigue is one of the common symptoms of chronic obstructive pulmonary disease (COPD) patients, which has a serious negative impact on their physiological function and mental health. This article reviewed the concept of fatigue, the effect of fatigue on COPD patients and the prevention and treatment methods of fatigue, which causes medical staff to pay attention to COPD related fatigue, in order to take effective and comprehensive intervention measures to alleviate the fatigue of COPD patients and improve the quality of life. (疲劳是慢性阻塞性肺疾病(COPD)患者常见症状之一, 对患者的生理功能及心理健康方面造成严重的负面影响。本文对疲劳的概念, 疲劳对COPD患者的影响以及疲劳的预防和治疗方法进行综述, 引起医务人员对COPD相关性疲劳的重视, 以采取有效、全面的干预措施缓解COPD患者的疲劳, 提高生活质量。)